(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Lexical anthropomorphism refers to the linguistic practice of attributing human-like characteristics, behaviors, or emotions to non-human entities such as animals, objects, or natural elements. One of the primary tools for achieving lexical anthropomorphism is figurative language, which includes devices such as metaphor, personification, and simile. This paper explores the role of figurative language in the construction of anthropomorphic imagery, focusing on how it allows non-human subjects to be imbued with human qualities. Through an examination of various examples in literature, advertising, and everyday discourse, this article demonstrates how figurative language serves as a bridge between human experience and the non-human world, fostering emotional engagement and enhancing meaning.